The challenges of online assessment amidst covid-19 pandemic disruption: The voice of EFL lecturers - Mariadi, Mariadi; Mirizon, Soni; Sitinjak, Margaretha Dinar (Universitas Islam Negeri Banda Aceh, 2022)
ABSTRACTSince the rapid spread of the Covid-19 pandemic, the government of Indonesia through the Ministry of Education and Culture has shifted the assessment mode from face-to-face into online assessment following the policy of online teaching and learning process. This conversion can essentially encourage the lecturers in higher education to reflect on and improve their assessment methods that are novel, stimulating, and practical for them. On the other hand, various kinds of challenges are likely to encounter by lecturers in carrying out the online assessment. This study aims to find out the challenges of online assessment in the midst of the Covid-19 pandemic disruption, and the solutions to meet these challenges. Qualitative method in a case study design was used to achieve the objectives of this study. The data were collected through in-depth interview and observation from two EFL lecturers at a state university in Palembang as the participants. The data were analysed by using thematic analysis. The findings revealed five primary challenges of online assessment: uneasiness, technical problems, time-consuming process, late submission, and academic dishonesty. Each of the challenges in the findings was followed by the solutions to deal with those challenges done by the participants. Keywords: Challenges of online assessment; Online assessment amidst Covid-19 pandemic; The voice of EFL lecturers.